Stable carbon isotope analysis of the diets of West African bovids in Pendjari Biosphere Reserve, Northern Benin - DJAGOUN, CHABI ADÉYÈMI SYLVESTRE; CODRON, Daryl; SEALY, J.; MENSAH, GUY APOLLINAIRE; SINSIN, Brice (My University, 2013)
Bovid diets have been studied for decades, but debate still exists about the diets of many species, in part because of geographical or habitat-related dietary variations. In this study we used stable carbon isotope analyses of faeces to explore the seasonal dietary preferences of 11 bovid species from a West African savanna, the Pendjari Biosphere Reserve (PBR), along the browser/grazer (or C3/C4) continuum.We compare our carbon isotope values with those for eastern and southern African bovids, as well as with dietary predictions based on continent-wide averages derived from field studies. Oribi and reedbuck, expected to be grazers were found to be predominantly C3-feeders (browsers) in the PBR. Bushbuck, common duiker and red-flanked duiker consumed more C4 grass than reported in previous studies. When comparing wet and dry season diets, kob, roan and oribi showed the least variation in C3 and C4 plant consumed proportions, while red-flanked duiker, bushbuck, reedbuck and waterbuck showed the most marked shifts. This study shows that animals in the betterstudied eastern and southern African savannas do not exhibit the full range of possible dietary adaptations. Inclusion of data from a wider geographical area to include less well-studied regions will inform our overall picture of bovid dietary ecology.
Keywords: diet; bovid; graze; browse; savanna